The role of natural killer T cells in liver transplantation - Zhao, Wenchao; Li, Mingqian; Song, Shifei; Zhi, Yao; Huan, Chen; Lv, Guoyue (Frontiers in Cell and Developmental Biology, 2024)
Natural killer T cells (NKTs) are innate-like lymphocytes that are abundant in the liver and participate in liver immunity. NKT cells express both NK cell and T cell markers, modulate innate and adaptive immune responses. Type I and Type II NKT cells are classified according to the TCR usage, while they recognize lipid antigen in a non-classical major histocompatibility (MHC) molecule CD1d-restricted manner. Once activated, NKT cells can quickly produce cytokines and chemokines to negatively or positively regulate the immune responses, depending on the different NKT subsets. In liver transplantation (LTx), the immune reactions in a series of processes determine the recipients’ long-term survival, including ischemia-reperfusion injury, alloresponse, and post-transplant infection. This review provides insight into the research on NKT cells subpopulations in LTx immunity during different processes, and discusses the shortcomings of the current research on NKT cells. Additionally, the CD56-expressing T cells are recognized as a NK-like T cell population, they were also discussed during these processes.